2005
DOI: 10.1002/bse.486
|View full text |Cite
|
Sign up to set email alerts
|

The Red Queen and the environment: reconciling public regulation and business strategy

Abstract: Until the late 1980s, environmental regulation in Denmark was often carried out in an intensely politicized and confrontational climate marked by strong tensions between authorities and polluting firms. In recent years, however, the general spirit of regulation seems to have improved significantly. During this same period, 'generic' measures such as general discharge limits have been supplemented with more specific demands, tailored for individual companies. The present paper presents a case study based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Firms that have built their strategic direction at least partly around a good environmental reputation are more likely to perceive a positive relationship between environmental investment and fi nancial performance and may not cut back on the former if economic circumstances become tighter. This would be in line with previous research that showed that fi rms' response to environmental regulation was guided by their strategic outlook (Søgaard and Madsen, 2005;Rugman and Verbeke, 2000).…”
Section: Environmental Regulation Economic Factors and Environmentalsupporting
confidence: 90%
See 1 more Smart Citation
“…Firms that have built their strategic direction at least partly around a good environmental reputation are more likely to perceive a positive relationship between environmental investment and fi nancial performance and may not cut back on the former if economic circumstances become tighter. This would be in line with previous research that showed that fi rms' response to environmental regulation was guided by their strategic outlook (Søgaard and Madsen, 2005;Rugman and Verbeke, 2000).…”
Section: Environmental Regulation Economic Factors and Environmentalsupporting
confidence: 90%
“…The current research thus seem to lend some further support to previous research that suggests that the strategic outlook of a fi rm will infl uence its response to economic and environmental regulation (cf. Søgaard and Madsen, 2005;Rugman and Verbeke, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This is necessary as BOER is directly related to the natural environment but is also closely intertwined with social and economic issues according to the particular context of firms and the scope of the regulation. For example, reducing air pollution directly impacts the health and welfare of people, especially in urban areas (Ghorani‐Azam, Riahi‐Zanjani, & Balali‐Mood, 2016); establishing an environmental regulation involves reaching agreements and collaboration among different stakeholders (Søgaard & Madsen, 2007); and complying with the regulation may affect competition at the industry level by increasing costs and improving innovation, with economic consequences for companies, employment, and society (Dechezleprêtre & Sato, 2017; Lanoie, Patry, & Lajeunesse, 2008). Our theoretical framework proposes a constraint order (environmental, social, and economic) in recognition of the fact that environmental restrictions are paramount as we just have one Earth; in consequence, social and economic arrangements must remain within the limits of the planetary boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations found that business may take several different directions in addressing new regulations (Potoski and Prakash, ; Prakash and Kollman, ). Some of the typical actions included aggressive exit strategies from markets, embracing closer collaboration and cooperation, public and private environmental partnerships, increased environmental management resources and heightened awareness of environmental impact (Potoski and Prakash, ; Prakash and Kollman, ; Lee and Rhee, ; Søgaard and Madsen, ; Clemens and Papadakis, ). Also, Clemens et al .…”
Section: Background Literaturementioning
confidence: 99%